Spraying sorbitol-chelated calcium affected foliar calcium absorption and promoted the yield of peanut (Arachis hypogaea L.) - Li, Tengsheng; Wei, Qianqian; Sun, Wei; Tan, Huiting; Cui, Yuzhao; Han, Chuanhao; Zhang, Huanyang; Zeng, Fanhe; Huang, Mingli; Yan, Dongyun (Frontiers in Plant Science, 2022)
The prevalent use of foliar calcium fertilizers in peanut production is inorganic, but calcium absorbed from the foliar has poor availability. Sorbitol-chelated calcium is a novel organic foliar calcium fertilizer that has rarely been studied for application in peanut production. To explore whether calcium absorption and peanut yields can be affected by foliar application of sorbitol-chelated calcium, this study conducted two field experiments using Virginia peanut (Huayu-22) in 2020 and 2021. The five spray treatments included: deionized water (CK), sorbitol (Sor), calcium nitrate (CaN), a mixture of sorbitol and calcium nitrate (SN), and sorbitol-chelated calcium (SC). The yield of peanuts treated with sorbitol-chelated calcium was increased by 12.31-16.63%, 10.22-11.83%, 6.31-9.69%, and 4.18-6.99% compared to the CK, Sor, CaN, and SN treatments, respectively. Sorbitol-chelated calcium had the lowest contact angle due to the wetting effect of sorbitol, which promoted calcium absorption by leaves. Sorbitol-chelated calcium improved the leaf calcium concentration by 13.12-19.32% and kernel calcium concentration by 6.49-8.15% compared to the CK treatment. Foliar fertilization increased the calcium concentration of each subcellular fraction of leaves and changed the distribution of calcium in mesophyll cells. This change was directly observed by transmission electron microscopy. Additionally, spraying sorbitol alone obtained similar effects to spraying calcium nitrate alone, indicating that the benefits of sorbitol itself were not negligible. The results of the principal component and correlation analysis showed that the increase in calcium concentrations and the change in calcium distribution improved the pod traits of the peanut, thus affecting the peanut yield. The above results showed that from the perspective of calcium absorption and distribution, sorbitol-chelated calcium is a more effective foliar calcium fortifier for peanuts and effectively improves peanut yields.